2018
DOI: 10.1101/414425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune differentiation regulator p100 tunes NF-κB responses to TNF

Abstract: Stringent regulation of TNF signaling prevents aberrant inflammation. TNF engages the canonical NF-κB pathway for activating the RelA:p50 heterodimer, which mediates specific expressions of pro-inflammatory and immune response genes. Importantly, the NF-κB system discriminates between time-varied TNF inputs. Negative feedback regulators of the canonical pathway, including IκBα, are thought to ensure transient RelA:p50 responses to brief TNF stimulations. The noncanonical NF-κB pathway controls a separate RelB … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Additionally, we observed that most of the genes in the adipocytokine signaling pathway have changed to varying degrees, and these genes are closely related to the NF-κB and MAPK signaling pathways. The NF-κB signaling pathway related genes TNF-α and FATCD36 are both decreased [33,34]. In addition, the transcription levels of STAT3, AMPK, Pgc-1α and Cpt1 are all increased (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, we observed that most of the genes in the adipocytokine signaling pathway have changed to varying degrees, and these genes are closely related to the NF-κB and MAPK signaling pathways. The NF-κB signaling pathway related genes TNF-α and FATCD36 are both decreased [33,34]. In addition, the transcription levels of STAT3, AMPK, Pgc-1α and Cpt1 are all increased (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The Relb promoter possesses a κB site, which directs RelA driven transcription, as well as a vitamin D receptor element (VDRE), which instructs vitamin D sensitive gene expression (Bren et al, 2001;Dong et al, 2003). Indeed, it was shown that the canonical RelA/NF-κB pathway is important for both basal as well as cytokine-induced expressions of RelB mRNA (Basak et al, 2008;Chatterjee et al, 2019). In contrast, vitamin D treatment caused Histone deacetylase 3 dependent transcriptional repression of Relb in dendritic cells (Dong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%